PENGEMBANGAN MEDIA PEMBELAJARAN PENYAKIT LANGKA BERBASIS MULTIMEDIA INTERAKTIF DENGAN METODE LUTHER - Elizabeth Christina; Sophia Deo Sandeva; Damiana Trivinita L. B; Andika Bayu S; Dasril Aldo (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The types of rare diseases are currently unknown to many people, especially the general public, due to a lack of information and outreach. Although this disease is very rare, there is a need for early education on its symptoms as a form of anticipation and information and tolerance for sufferers of this disease with the aim of increasing knowledge and awareness about rare diseases. The main problem in this study is the lack of information media for health education about rare diseases, so we need an information media that can present rare disease knowledge that is not only easy to understand but also creative in order to be able to attract people's attention and make learning more fun by creating a interactive multimedia-based learning system. This application is to support understanding of rare diseases, especially for ordinary people who suffer from rare diseases or are around people with rare diseases. The method chosen is the Luther method, which is a multimedia development method based on six stages, namely Concept, Design, Material Collection, Assembly, Testing, and Distribution.